DEVELOPMENT OF COMPETENCY-BASED TRAINING MODELS FOR EXPERIENTIAL LEARNING FACILITATORS IN INDONESIA - Haryono, Hendro; Latupapua, Conchita V.; Heriani, Heriani (INFOKUM, 2022)
This study aimed to research and develop a competency-based training model for experiential learning facilitators, create a program design, and test the validity, practicality, and effectiveness of the developed training model. This type of research uses Research and Development (R&D) with an analytical method using 10 steps Borg and Gall. The research method used is a mixed research or sequential mixed methods with the number of samples tested as many as 71 respondents. Field trials were carried out in three locations, namely the city of Samarinda (Kaltim), Kab. Pasuruan (East Java), and the City of Jogjakarta (DIY). The product resulting from this research is a training model based on SKKNI outbound scouting/experiential learning facilitator, which includes: curriculum, syllabus, lesson plan, list of equipment and materials, post-training evaluation form, pretest and posttest questions, list of tasks/practices, supporting questions observation, power point slides for presentation materials, and learning material books. The test results show that the training model developed is valid, practical, and effective with a N-Gain score of 0.59 or quite effective.